2010
DOI: 10.1177/1363459309360794
|View full text |Cite
|
Sign up to set email alerts
|

When resources get sparse: A longitudinal, qualitative study of emotions, coping and resource-creation when parenting a young child with severe disabilities

Abstract: Parents who realize that their newborn child is severely disabled often experience severe physical and emotional stress. Parental well-being is essential for the care-taking of the child. It is yet not known why some cope well and others do not. The aim of this study was to explore how parents coped with parenting a disabled child and how they maintained their energy and personal resources. We explored parents' experiences, coping and resources over a two-year period after their child was diagnosed with a seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 45 publications
2
60
0
1
Order By: Relevance
“…Hastings and Taunt (2002) have also suggested the usefulness of conceptualising positive perceptions as a style of coping in parents who have a child with a developmental disability. This type of positive reappraisal has been demonstrated in other studies where a parent has a child with a severe disability (Graungaard et al 2011). Parents turned their experiences into resources such as engaging with hope.…”
Section: Discussionmentioning
confidence: 56%
“…Hastings and Taunt (2002) have also suggested the usefulness of conceptualising positive perceptions as a style of coping in parents who have a child with a developmental disability. This type of positive reappraisal has been demonstrated in other studies where a parent has a child with a severe disability (Graungaard et al 2011). Parents turned their experiences into resources such as engaging with hope.…”
Section: Discussionmentioning
confidence: 56%
“…Mothers of children with chronic illnesses are found to be at risk of psychosocial problems (Barlow et al 1998) and mothers of children with disabilities or chronic illness experience high levels of stress (Burton et al 2008b;Miodrag and Hodapp 2010), depression (Singer 2006) and burnout (Pelchat, Lefebvre, and Levert 2007). Caregivers in this role must manage many different stressors (Hauskov-Graungaard et al 2011) and manage a high care burden (Miodrag and Hodapp 2010).…”
Section: Review Findingsmentioning
confidence: 97%
“…In research examining Canadian mothers of African and Caribbean descent raising children with sickle cell disease (Burnes et al 2008), mothers complained of mental health concerns as well as difficulties coping with stigma in combination with racism. Coping strategies such as positive reframing, the use of informational and social support (Hauskov-Graungaard et al 2011) are identified as essential to maternal well-being. Informational support is understood to reduce maternal stress where there are disabled children (Miller et al 1992).…”
Section: Review Findingsmentioning
confidence: 99%
“…It proved robust for facilitating the organisation of material, and the 'scaffolding' it provided (Morse & Richards, cited in J. M. Morse & Mitcham, 2002) did not need to be dismantled in the light of the emerging data; rather, the framework provided neutral boundaries within which the internal structures of the concepts could emerge, in the form of various subthemes. Additional themes also emerged, such as the place of emotions, and the richness of these warrants discussion in a further article, adding to recent findings by Graungaard et al (2011) on coping by parents of children with severe disabilities. The method we used avoided 're-inventing the wheel', by drawing upon the extensive attributions literature, while also permitting new information to emerge.…”
Section: Discussionmentioning
confidence: 85%